Adhesive film for circuit connection, circuit connection structure, and method for manufacturing the same
Patent Information
- Application Number
- JP2023141098
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2025-03-13
AI Technical Summary
【0010】 本開示によれば、接続信頼性に優れる回路接続構造体を形成することが可能な回路接続用接着剤フィルムが開示される。このような回路接続用接着剤フィルムは、低温(例えば、120~170℃)で低圧(例えば、バンプ電極での面積換算圧力25MPa以下)で実装することが可能であり、COP実装に好適に用いることができる。また、本開示によれば、このような回路接続用接着剤フィルムを用いた回路接続構造体及びその製造方法が開示される。
Smart Images

Figure 2025034613000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an adhesive film for circuit connection, as well as a circuit connection structure and a method for producing the same. [Background technology]
[0002] Conventionally, liquid crystal display panels, organic EL panels, etc. have been used as various display means for televisions, PC monitors, mobile phones, smartphones, etc. In such display devices, from the viewpoints of fine pitch, light weight and thinness, so-called COG (chip on glass) mounting is adopted in which a driving IC is mounted directly on the glass substrate of the display panel.
[0003] In a liquid crystal display panel in which the COG mounting method is adopted, for example, a semiconductor element such as a liquid crystal driving IC is connected on a transparent substrate (such as a glass substrate) having a plurality of transparent electrodes (such as ITO (indium tin oxide)). As an adhesive material for connecting the electrode terminals of the semiconductor element and the transparent electrodes, an anisotropically conductive circuit connection adhesive film in which conductive particles are dispersed in the adhesive is used. For example, when mounting a liquid crystal driving IC as a semiconductor element, the liquid crystal driving IC has a plurality of electrode terminals corresponding to the transparent electrodes on its mounting surface, and the liquid crystal driving IC is thermocompression-bonded onto the transparent substrate via the anisotropically conductive circuit connection adhesive film, whereby the electrode terminals and the transparent electrodes are connected to obtain a circuit connection structure.
[0004] In recent years, displays with curved surfaces (flexible displays) have been proposed. In such flexible displays, flexible plastic substrates (polyimide substrates, etc.) are used as substrates instead of glass substrates, and various electronic components such as driving ICs are also mounted on the plastic substrates. As a method of such mounting, COP (chip on plastic) mounting using an adhesive film for circuit connection having anisotropic conductivity has been considered (for example, see Patent Document 1). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2016-054288 A Summary of the Invention [Problem to be solved by the invention]
[0006] In COP mounting, from the viewpoint of suppressing deformation of the plastic substrate during mounting, mounting at low temperature (e.g., 120 to 170°C) and low pressure (e.g., area-equivalent pressure of 25 MPa or less at bump electrodes) is desired. However, when mounting is performed under such conditions, the connection reliability of the obtained circuit connection structure may be insufficient due to a decrease in resin fluidity caused by the low temperature and a decrease in resin expulsion caused by the low pressure.
[0007] Therefore, a primary object of the present disclosure is to provide an adhesive film for circuit connection that is capable of forming a circuit connection structure with excellent connection reliability. [Means for solving the problem]
[0008] The inventors conducted studies to solve the above problems and discovered that by making the adhesive film for circuit connection contain specified components in specified proportions, the melt viscosity of the adhesive film for circuit connection can be reduced, and even in low-temperature, low-pressure mounting, a decrease in resin fluidity and a decrease in resin removal properties can be suppressed, thereby improving the connection reliability of the resulting circuit connection structure, thereby completing the invention of the present disclosure.
[0009] The present disclosure provides an adhesive film for circuit connection according to any one of [1] to [6], a method for producing a circuit connection structure according to [7], and a circuit connection structure according to [8]. [1] An adhesive film for circuit connection comprising a first adhesive layer containing conductive particles and a second adhesive layer provided on the first adhesive layer, the second adhesive layer containing a thermosetting resin component and a thermoplastic resin, the thermosetting resin component containing an alicyclic epoxy compound, and a content of the thermoplastic resin being 50 parts by mass or less per 100 parts by mass of a total mass of the alicyclic epoxy compound. [2] The adhesive film for circuit connection described in [1], wherein the total content of the alicyclic epoxy compound and the thermoplastic resin is 15 mass% or more, based on the total mass of the second adhesive layer. [3] The adhesive film for circuit connection according to [1] or [2], wherein the thermosetting resin component contains, as the alicyclic epoxy compound, a first alicyclic epoxy compound that is liquid at 25°C and a second alicyclic epoxy compound that is solid at 25°C. [4] The adhesive film for circuit connection according to [3], wherein the content of the thermoplastic resin is 120 parts by mass or less per 100 parts by mass of the total mass of the second alicyclic epoxy compound. [5] The adhesive film for circuit connection according to [3] or [4], wherein the content of the thermoplastic resin is 50 parts by mass or more per 100 parts by mass of the total mass of the first alicyclic epoxy compound. [6] The adhesive film for circuit connection according to any one of [1] to [5], wherein the thermosetting resin component further contains a cationically polymerizable compound other than the alicyclic epoxy compound. [7] A method for producing a circuit connection structure, comprising the steps of: interposing an adhesive film for circuit connection according to any one of [1] to [6] between a first circuit member having a first electrode and a second circuit member having a second electrode; and thermocompression bonding the first circuit member and the second circuit member to electrically connect the first electrode and the second electrode to each other. [8] A circuit connection structure comprising: a first circuit member having a first electrode; a second circuit member having a second electrode; and a circuit connection portion disposed between the first circuit member and the second circuit member and electrically connecting the first electrode and the second electrode to each other, wherein the circuit connection portion comprises a cured product of the adhesive film for circuit connection according to any one of [1] to [6]. Effect of the Invention
[0010] According to the present disclosure, there is disclosed an adhesive film for circuit connection capable of forming a circuit connection structure having excellent connection reliability. Such an adhesive film for circuit connection can be mounted at low temperature (e.g., 120 to 170°C) and low pressure (e.g., equivalent surface area pressure of 25 MPa or less at a bump electrode), and can be suitably used for COP mounting. Furthermore, according to the present disclosure, there is disclosed a circuit connection structure using such an adhesive film for circuit connection and a method for producing the same. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a schematic cross-sectional view showing one embodiment of an adhesive film for circuit connection. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing another embodiment of the adhesive film for circuit connection. [Diagram 3] FIG. 3 is a schematic cross-sectional view showing one embodiment of a circuit connection structure. [Figure 4] 4(a) and 4(b) are schematic cross-sectional views showing one embodiment of a method for producing a circuit connection structure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, an embodiment of the present disclosure will be described in detail with reference to the drawings. In the following description, the same or corresponding parts are denoted by the same reference numerals, and duplicated descriptions will be omitted. Note that the present disclosure is not limited to the following embodiment.
[0013] In this specification, the numerical range indicated by using "~" indicates a range including the numerical values described before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in stages in this specification, the upper limit or lower limit of a certain stage may be replaced with the upper limit or lower limit of the numerical range of another stage. In addition, in the numerical ranges described in this specification, the upper limit or lower limit of the numerical range may be replaced with a value shown in the examples. In addition, the upper limit and lower limit values described individually can be arbitrarily combined. In the expression of a numerical range "A~B", the numerical values A and B at both ends are included in the numerical range as the lower limit and upper limit, respectively. In this specification, for example, the description "10 or more" means "10" and "a numerical value exceeding 10", and the same applies when the numerical values are different. In addition, for example, the description "10 or less" means "10" and "a numerical value less than 10", and the same applies when the numerical values are different.
[0014] In this specification, "(meth)acrylate" means at least one of acrylate and the corresponding methacrylate. The same applies to other similar expressions such as "(meth)acryloyl" and "(meth)acrylic acid". In addition, "A or B" may include either A or B, or may include both.
[0015] In this specification, the materials exemplified below may be used alone or in combination of two or more, unless otherwise specified. When a plurality of substances corresponding to each component are present in the composition, the content of each component in the composition means the total amount of the plurality of substances present in the composition, unless otherwise specified.
[0016] [Adhesive film for circuit connection] The adhesive film for circuit connection comprises a first adhesive layer containing conductive particles and a second adhesive layer provided on the first adhesive layer. The first adhesive layer may further contain a cured product of a photocurable resin component and a first thermosetting resin component. The second adhesive layer contains a thermosetting resin component (second thermosetting resin component) and a thermoplastic resin.
[0017] Fig. 1 is a schematic cross-sectional view showing one embodiment of an adhesive film for circuit connection, and is a diagram showing a schematic longitudinal section of the adhesive film for circuit connection. The adhesive film for circuit connection 10A shown in Fig. 1 comprises a first adhesive layer 1 containing a plurality of conductive particles 4 and an adhesive component 3, and a second adhesive layer 2 provided on the first adhesive layer 1. In this specification, the "longitudinal section" means a section (a section in the thickness direction) perpendicular to the main surface (e.g., the adhesive film for circuit connection 10A).
[0018] At least a part of the conductive particles 4 may be arranged in the horizontal direction in the longitudinal section of the circuit connection adhesive film 10A, with adjacent conductive particles spaced apart from each other. In other words, the circuit connection adhesive film 10A may be configured with a central region 10a in which the conductive particles 4 are arranged in the horizontal direction in a state where they are spaced apart from adjacent conductive particles in the longitudinal section, and surface side regions 10b and 10c in which no conductive particles 4 are present. Here, the "horizontal direction" means a direction parallel to the main surface of the circuit connection adhesive film (the left-right direction in FIG. 1). In FIG. 1, some of the conductive particles 4 are exposed from the surface of the first adhesive layer 1 (for example, protruding toward the second adhesive layer 2), but the conductive particles 4 may be entirely embedded in the first adhesive layer 1 so that they are not exposed from the surface of the first adhesive layer 1.
[0019] The adhesive film 10A for circuit connection may have conductive particles 4 dispersed in the first adhesive layer 1. Therefore, the adhesive film 10A for circuit connection may be an adhesive film for circuit connection having anisotropic conductivity (anisotropic conductive adhesive film). The adhesive film 10A for circuit connection may be interposed between a first circuit member having a first electrode and a second circuit member having a second electrode, and may be used to electrically connect the first electrode and the second electrode to each other by thermocompression bonding the first circuit member and the second circuit member. Note that "anisotropic conductivity" means that the film is conductive in the pressure direction and is insulating in the non-pressure direction.
[0020] <First adhesive layer> The first adhesive layer 1 contains conductive particles 4 (hereinafter, sometimes referred to as "component (A)"), and may further contain a cured product of a photocurable resin component (hereinafter, sometimes referred to as "component (B)") and a thermosetting resin component (hereinafter, sometimes referred to as "component (C)"). The cured product of component (B) may be a cured product obtained by completely curing component (B), or may be a cured product obtained by curing a part of component (B). Component (C) is a component that can flow when connected, and is, for example, an uncured curable component (e.g., a resin component). The components other than the conductive particles 4 constituting the first adhesive layer 1 are, for example, components that do not have electrical conductivity (e.g., an insulating resin component).
[0021] (A) Component: Conductive particles The component (A) is not particularly limited as long as it is a particle having electrical conductivity, and may be a metal particle composed of a metal such as Au, Ag, Pd, Ni, Cu, or solder, or a conductive carbon particle composed of conductive carbon. The component (A) may be a coated conductive particle having a core containing non-conductive glass, ceramic, plastic (polystyrene, etc.), or the like, and a coating layer containing the above metal or the above conductive carbon and coating the core. Among these, the component (A) is preferably a coated conductive particle having a core containing plastic and a coating layer containing a metal or conductive carbon and coating the core, or a metal particle formed of a heat-fusible metal.
[0022] When component (A) is a coated conductive particle, the cured product of the thermosetting resin component can be easily deformed by heating or applying pressure. This increases the contact area between the electrodes and component (A) when electrically connecting the electrodes, thereby further improving the conductivity between the electrodes.
[0023] When component (A) is metal particles formed from a heat-fusible metal, the connection between the electrodes tends to be stronger. This tendency is particularly noticeable when solder particles are used as component (A).
[0024] The solder particles may contain at least one selected from the group consisting of tin, a tin alloy, indium, and an indium alloy, from the viewpoint of achieving both connection strength and a low melting point. Also, the solder particles may contain at least one selected from the group consisting of an In-Bi alloy, an In-Sn alloy, an In-Sn-Ag alloy, an Sn-Au alloy, an Sn-Bi alloy, an Sn-Bi-Ag alloy, an Sn-Ag-Cu alloy, and an Sn-Cu alloy, from the viewpoint of obtaining higher reliability during a high-temperature high-humidity test and a thermal shock test.
[0025] The component (A) may be an insulating coated conductive particle comprising the above-mentioned metal particle, the above-mentioned conductive carbon particle, or the above-mentioned coated conductive particle, and an insulating layer containing an insulating material such as a resin and coating the surface of the particle. When the component (A) is an insulating coated conductive particle, even if the content of the component (A) is high, the particle surface has an insulating layer, so that the occurrence of a short circuit due to contact between the components (A) can be suppressed, and the insulation between adjacent electrode circuits can also be improved.
[0026] The maximum particle size of the (A) component must be smaller than the minimum distance between the electrodes (the shortest distance between adjacent electrodes). The maximum particle size of the (A) component may be 1.0 μm or more, 2.0 μm or more, or 2.5 μm or more from the viewpoint of excellent dispersibility and conductivity. The maximum particle size of the (A) component may be 30.0 μm or less, 25.0 μm or less, 20.0 μm or less, 15.0 μm or less, 10.0 μm or less, or 5.0 μm or less from the viewpoint of excellent dispersibility and conductivity. In this specification, the particle size of any 300 pieces (pcs) of the (A) component in the first adhesive layer is measured by observation using a scanning electron microscope (SEM), and the largest value obtained is defined as the maximum particle size of the (A) component. Note that when the (A) component has protrusions or the like and is not spherical, the particle size of the (A) component is defined as the diameter of a circle circumscribing the conductive particle in the SEM image.
[0027] From the viewpoint of excellent dispersibility and electrical conductivity, the average particle size of the (A) component may be 1.0 μm or more, 2.0 μm or more, 2.5 μm or more, or 3.0 μm or more. From the viewpoint of excellent dispersibility and electrical conductivity, the average particle size of the (A) component may be 20.0 μm or less, 10.0 μm or less, 7.0 μm or less, or 5.0 μm or less. In this specification, the particle size of any 300 pieces (pcs) of the (A) component in the first adhesive layer is measured by observation using a scanning electron microscope (SEM), and the average value of the obtained particle sizes is defined as the average particle size.
[0028] The component (A) is preferably uniformly dispersed in the first adhesive layer 1. From the viewpoint of obtaining a stable connection resistance, the particle density of the component (A) in the adhesive film for circuit connection 10A is preferably 100 particles / mm 2 More than 1000 pieces / mm 2 More than 3000 pieces / mm 2 More than 5000 pieces / mm 2 More than 7000 pieces / mm 2 More than 10000 pieces / mm 2 or more than 12000 pieces / mm 2 From the viewpoint of improving the insulating properties between adjacent electrodes, the particle density of the component (A) in the adhesive film for circuit connection 10A may be 100,000 particles / mm 2 Below, 70000 pieces / mm 2 Below, 50000 pieces / mm 2 Below 30000 pieces / mm 2 or less than 20,000 pieces / mm 2 It may be the following:
[0029] The monodispersity of the (A) component in the circuit connection adhesive film 10A may be 90% or more. When the monodispersity of the (A) component is in this range, short circuit defects between adjacent circuits are unlikely to occur, and a circuit connection structure with sufficiently high connection reliability tends to be obtained. The monodispersity of the (A) component may be 92% or more, 94% or more, 96% or more, 97% or more, 98% or more, or 99% or more. The upper limit of the monodispersity may be 100%. The monodispersity can be calculated, for example, by observing the circuit connection adhesive film 10A from the first adhesive layer side at a magnification of 200 times using a metal microscope, and measuring the number of the (A) component in the circuit connection adhesive film 10A according to the following formula. Monodispersion rate (%) = (2500 μm 2 Number of monodispersed conductive particles in / 2500μm 2 (number of conductive particles in) x 100
[0030] The content of the (A) component may be 5 mass% or more, 10 mass% or more, or 20 mass% or more based on the total mass of the first adhesive layer from the viewpoint of further improving the electrical conductivity. The content of the (A) component may be 60 mass% or less, 50 mass% or less, or 45 mass% or less based on the total mass of the first adhesive layer from the viewpoint of easily suppressing a short circuit. When the content of the (A) component is in the above range, the effects of the present disclosure tend to be significantly exhibited.
[0031] (B) Component: Photocurable resin component The (B) component is not particularly limited as long as it is a resin component that is cured by light irradiation, but when the (C) component is a resin component having cationic curability, the (B) component may be a resin component having radical curability from the viewpoint of better connection resistance. The (B) component may contain, for example, a radical polymerizable compound (hereinafter sometimes referred to as "(B1) component") and a photoradical polymerization initiator (hereinafter sometimes referred to as "(B2) component"). The (B) component may be a component consisting of the (B1) component and the (B2) component.
[0032] Component (B1): radically polymerizable compound The component (B1) is a compound that is polymerized by radicals generated from the component (B2) upon irradiation with light (e.g., ultraviolet light). The component (B1) may be either a monomer or a polymer (or oligomer) formed by polymerization of one or more types of monomers.
[0033] The (B1) component is a compound having a radical polymerizable group that reacts with a radical. Examples of the radical polymerizable group include a (meth)acryloyl group, a vinyl group, an allyl group, a styryl group, an alkenyl group, an alkenylene group, and a maleimide group. The number of radical polymerizable groups (the number of functional groups) possessed by the (B1) component may be 2 or more from the viewpoint of easily obtaining a desired melt viscosity after polymerization and being more excellent in connection reliability, and may be 10 or less, 6 or less, or 4 or less from the viewpoint of further improving the effect of reducing the connection resistance and suppressing the cure shrinkage during polymerization. In addition, in order to balance the crosslink density and the cure shrinkage, in addition to the compound having the number of radical polymerizable groups within the above range, a compound having the number of radical polymerizable groups outside the above range may be used.
[0034] The (B1) component contains a polyfunctional (two or more functional) (meth)acrylate from the viewpoint of suppressing the flow of the conductive particles. The polyfunctional (two or more functional) (meth)acrylate may be a bifunctional or trifunctional (meth)acrylate, and is preferably a bifunctional (meth)acrylate. The bifunctional (meth)acrylate may be a bifunctional aromatic (meth)acrylate.
[0035] Examples of polyfunctional (meth)acrylates include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, tetrapropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, ethoxylated polypropylene glycol di(meth)acrylate, 1,3-butane aliphatic (meth)acrylates such as diol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 3-methyl-1,5-pentanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 2-butyl-2-ethyl-1,3-propanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, glycerin di(meth)acrylate, tricyclodecane dimethanol (meth)acrylate, and ethoxylated 2-methyl-1,3-propanediol di(meth)acrylate;Aromatic (meth)acrylates such as ethoxylated bisphenol A di(meth)acrylate, propoxylated bisphenol A di(meth)acrylate, ethoxylated propoxylated bisphenol A di(meth)acrylate, ethoxylated bisphenol F di(meth)acrylate, propoxylated bisphenol F di(meth)acrylate, ethoxylated propoxylated bisphenol F di(meth)acrylate, ethoxylated fluorene di(meth)acrylate, propoxylated fluorene di(meth)acrylate, ethoxylated propoxylated fluorene di(meth)acrylate, trimethylolpropane tri(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, propoxylated trimethylolpropane tri(meth)acrylate, ethoxylated propoxylated trimethylolpropane tri(meth)acrylate, pentaerythritol aliphatic (meth)acrylates such as pentaerythritol tri(meth)acrylate, ethoxylated pentaerythritol tri(meth)acrylate, propoxylated pentaerythritol tri(meth)acrylate, ethoxylated propoxylated pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, ethoxylated pentaerythritol tetra(meth)acrylate, propoxylated pentaerythritol tetra(meth)acrylate, ethoxylated propoxylated pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetraacrylate, and dipentaerythritol hexa(meth)acrylate; aromatic epoxy (meth)acrylates such as bisphenol-type epoxy (meth)acrylate, phenol novolac-type epoxy (meth)acrylate, and cresol novolac-type epoxy (meth)acrylate;
[0036] From the viewpoint of achieving both the effect of reducing the connection resistance and the suppression of particle flow, the content of the polyfunctional (difunctional or higher) (meth)acrylate may be, for example, 50 to 100 mass%, 70 to 100 mass%, or 90 to 100 mass%, or may be 100 mass%, based on the total mass of the (B1) component.
[0037] The (B1) component may further contain a monofunctional (meth)acrylate in addition to the polyfunctional (two or more functional) (meth)acrylate. Examples of the monofunctional (meth)acrylate include (meth)acrylic acid, methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, butoxyethyl (meth)acrylate, isoamyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, heptyl (meth)acrylate, octylheptyl (meth)acrylate, nonyl (meth)acrylate, Decyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-chloro-2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, ethoxypolyethylene glycol (meth)acrylate, methoxypolypropylene glycol (meth)acrylate, ethoxypolypropylene glycol (meth)acrylate, mono(2-(meth)acryloyloxy) aliphatic (meth)acrylates such as diethyl succinate; benzyl (meth)acrylate, phenyl (meth)acrylate, o-biphenyl (meth)acrylate, 1-naphthyl (meth)acrylate, 2-naphthyl (meth)acrylate, phenoxyethyl (meth)acrylate, p-cumylphenoxyethyl (meth)acrylate, o-phenylphenoxyethyl (meth)acrylate, 1-naphthoxyethyl (meth)acrylate, 2-naphthyl (meth)acrylate, phenoxypolyether aromatic (meth)acrylates such as ethylene glycol (meth)acrylate, nonylphenoxy polyethylene glycol (meth)acrylate, phenoxy polypropylene glycol (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2-hydroxy-3-(o-phenylphenoxy)propyl (meth)acrylate, 2-hydroxy-3-(1-naphthoxy)propyl (meth)acrylate, and 2-hydroxy-3-(2-naphthoxy)propyl (meth)acrylate;Examples of such methacrylates include (meth)acrylates having an epoxy group such as glycidyl (meth)acrylate, (meth)acrylates having an alicyclic epoxy group such as 3,4-epoxycyclohexylmethyl (meth)acrylate, and (meth)acrylates having an oxetanyl group such as (3-ethyloxetan-3-yl)methyl (meth)acrylate.
[0038] The content of the monofunctional (meth)acrylate based on the total mass of the component (B1) may be, for example, 0 to 50 mass %, 0 to 30 mass %, or 0 to 10 mass %, or may be 0 mass %.
[0039] The cured product of the (B) component may have a polymerizable group that reacts with other than radicals. The polymerizable group that reacts with other than radicals may be, for example, a cationic polymerizable group that reacts with cations. Examples of the cationic polymerizable group include epoxy groups such as glycidyl groups, alicyclic epoxy groups such as epoxycyclohexylmethyl groups, and oxetanyl groups such as ethyloxetanylmethyl groups. The cured product of the (B) component having a polymerizable group that reacts with other than radicals can be introduced by using, as the (B) component, a (meth)acrylate having a polymerizable group that reacts with other than radicals, such as a (meth)acrylate having an epoxy group, a (meth)acrylate having an alicyclic epoxy group, or a (meth)acrylate having an oxetanyl group. The mass ratio of the (meth)acrylate having a polymerizable group that reacts by other than radicals to the total mass of the component (B1) (mass (feed amount) of the (meth)acrylate having a polymerizable group that reacts by other than radicals / total mass (feed amount) of the component (B1)) may be, for example, 0 to 0.7, 0 to 0.5, or 0 to 0.3 from the viewpoint of improving reliability.
[0040] The (B1) component may contain other radical polymerizable compounds in addition to polyfunctional (bifunctional or higher) and monofunctional (meth)acrylates. Examples of other radical polymerizable compounds include maleimide compounds, vinyl ether compounds, allyl compounds, styrene derivatives, acrylamide derivatives, and nadimide derivatives. The content of the other radical polymerizable compounds may be, for example, 0 to 40% by mass based on the total mass of the (B1) component.
[0041] Component (B2): Photoradical polymerization initiator The component (B2) is a photopolymerization initiator that generates radicals when irradiated with light having a wavelength in the range of 150 to 750 nm, preferably light having a wavelength in the range of 254 to 405 nm, and more preferably light having a wavelength of 365 nm (e.g., ultraviolet light).
[0042] The component (B2) is decomposed by light to generate free radicals. That is, the component (B2) is a compound that generates radicals by applying light energy from the outside. The component (B2) may be a compound having an oxime ester structure, a bisimidazole structure, an acridine structure, an α-aminoalkylphenone structure, an aminobenzophenone structure, an N-phenylglycine structure, an acylphosphine oxide structure, a benzyl dimethyl ketal structure, an α-hydroxyalkylphenone structure, or the like. From the viewpoint of easily obtaining a desired melt viscosity and from the viewpoint of being more effective in reducing the connection resistance, the component (B2) may be a compound having at least one structure selected from the group consisting of an oxime ester structure, an α-aminoalkylphenone structure, and an acylphosphine oxide structure.
[0043] Specific examples of compounds having an oxime ester structure include 1-phenyl-1,2-butanedione-2-(o-methoxycarbonyl)oxime, 1-phenyl-1,2-propanedione-2-(o-methoxycarbonyl)oxime, 1-phenyl-1,2-propanedione-2-(o-ethoxycarbonyl)oxime, 1-phenyl-1,2-propanedione-2-o-benzoyloxime, 1,3-diphenylpropanetrione-2-(o-ethoxycarbonyl)oxime, 1-phenyl-3-ethoxypropanetrione-2-(o-benzoyl)oxime, 1,2-octanedione, 1-[4-(phenylthio)phenyl-, 2-(o-benzoyloxime)], ethanone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-, 1-(o-acetyloxime), and the like.
[0044] Specific examples of compounds having an α-aminoalkylphenone structure include 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-morpholinophenyl)-butanone-1, and the like.
[0045] Specific examples of compounds having an acylphosphine oxide structure include bis(2,6-dimethoxybenzoyl)-2,4,4-trimethyl-pentylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.
[0046] The content of the (B2) component may be, for example, 0.1 to 10 parts by mass, 0.3 to 7 parts by mass, or 0.5 to 5 parts by mass per 100 parts by mass of the (B1) component from the viewpoint of suppressing the flow of the conductive particles.
[0047] The content of the cured product of the (B) component may be 1 mass% or more, 3 mass% or more, or 5 mass% or more based on the total mass of the first adhesive layer from the viewpoint of suppressing the flow of the conductive particles. The content of the cured product of the (B) component may be 40 mass% or less, 30 mass% or less, or 20 mass% or less based on the total mass of the first adhesive layer from the viewpoint of exhibiting low resistance in low-pressure mounting. When the content of the cured product of the (B) component is in the above range, the effects of the present disclosure tend to be significantly exhibited.
[0048] (C) Component: Thermosetting resin component The (C) component is not particularly limited as long as it is a resin component that is cured by heat, but when the (B) component is a resin component having radical curing properties, the (C) component may be a resin component having cationic curing properties from the viewpoint of being superior in terms of connection resistance. The (C) component may contain, for example, a cationic polymerizable compound (hereinafter, sometimes referred to as "(C1) component") and a thermal cationic polymerization initiator (hereinafter, sometimes referred to as "(C2) component"). The (C) component may be a component consisting of the (C1) component and the (C2) component. The first thermosetting resin component, the second thermosetting resin component, and the third thermosetting resin component mean the thermosetting resin components contained in the first adhesive layer, the second adhesive layer, and the third adhesive layer, respectively, and the components (e.g., the (C1) component, the (C2) component, etc.) and the contents contained in the first thermosetting resin component, the second thermosetting resin component, and the third thermosetting resin component may be the same as or different from each other.
[0049] Component (C1): Cationic polymerizable compound The (C1) component is a compound that crosslinks by reacting with the (C2) component by heat. The (C1) component means a compound (resin) that does not have a radically polymerizable group that reacts by radicals, and the (C1) component is not included in the (B1) component. Examples of the (C1) component include compounds having a cyclic ether group, such as epoxy compounds and oxetane compounds. From the viewpoint of further improving the effect of reducing the connection resistance and achieving better connection reliability, the (C1) component may contain, for example, an alicyclic epoxy compound (a compound having a partial structure in which the carbon atoms constituting the epoxy group directly constitute an alicyclic ring) (hereinafter, sometimes referred to as "(C1-1) component").
[0050] The component (C1-1) can be any compound having an alicyclic epoxy group (e.g., an epoxycyclohexyl group) and no radical polymerizable group. The component (C1-1) may have a cyclic ether group (structure) other than an alicyclic epoxy group (e.g., an epoxy group (structure), an oxetanyl group (structure), etc.). The component (C1-1) may be a first alicyclic epoxy compound (hereinafter sometimes referred to as "component (C1-1a)") that is liquid at 25°C, or a second alicyclic epoxy compound (hereinafter sometimes referred to as "component (C1-1b)") that is solid at 25°C, or a combination thereof.
[0051] The component (C1-1a) may be, for example, an alicyclic epoxy compound having a softening point of 40° C. or less. The component (C1-1b) may be, for example, an alicyclic epoxy compound having a softening point of more than 40° C. The softening point means a value measured by the ring and ball method in accordance with JIS K7234:1986.
[0052] Examples of commercially available products of the component (C1-1a) include Celloxide 2021P (trade name, manufactured by Daicel Corporation), Celloxide 8010 (trade name, manufactured by Daicel Corporation), and Celloxide 2081 (trade name, manufactured by Daicel Corporation).
[0053] Other examples of the component (C1-1a) include compounds represented by general formula (I).
[0054] [ka]
[0055] In formula (I), R 1 , R 2 , R 3 , and R 4 each independently represents a hydrogen atom or a methyl group, and m and n each independently represent 1 or 2.
[0056] An example of a commercially available product of the component (C1-1b) is EHPE3150 (product name, manufactured by Daicel Corporation, softening point: 75° C.).
[0057] In addition to the component (C1-1), the component (C1) may contain a cationic polymerizable compound other than the component (C1-1) (hereinafter, sometimes referred to as "component (C1-2)"). The component (C1-2) can be any compound that has a cyclic ether group other than an alicyclic epoxy group and does not have an alicyclic epoxy group without any particular restrictions. The component (C1-2) may be, for example, a compound that has an oxetanyl group and does not have an alicyclic epoxy group.
[0058] Commercially available products of the component (C1-2) include, for example, ETERNACOLL OXBP (trade name, 4,4'-bis[(3-ethyl-3-oxetanyl)methoxymethyl]biphenyl, manufactured by UBE Corporation), OXSQ, OXT-121, OXT-221, OXT-101, and OXT-212 (trade names, manufactured by Toagosei Co., Ltd.).
[0059] Other examples of the component (C1-2) include bifunctional epoxy resins such as bisphenol A type epoxy resins, novolac type epoxy resins such as phenol novolac type epoxy resins, and cresol novolac type epoxy resins.
[0060] Component (C2): Thermal cationic polymerization initiator The component (C2) is a thermal polymerization initiator that generates an acid or the like when heated to initiate polymerization. The component (C2) may be a salt compound composed of a cation and an anion. The component (C2) is, for example, BF4 - , BR4 - (R represents a phenyl group in which hydrogen atoms are substituted with two or more fluorine atoms or two or more trifluoromethyl groups), PF6 - , SbF6 - , AsF6 - and onium salts such as sulfonium salts, phosphonium salts, ammonium salts (quaternary ammonium salts), diazonium salts, iodonium salts, anilinium salts, and pyridinium salts having an anion such as those mentioned above.
[0061] From the viewpoint of storage stability, the component (C2) is, for example, an anion containing boron as a constituent element, i.e., BF4 - or BR4 - (R represents a phenyl group in which a hydrogen atom is substituted with two or more fluorine atoms or two or more trifluoromethyl groups). The anion containing boron as a constituent element is BR4 - and more specifically, tetrakis(pentafluorophenyl)borate.
[0062] The onium salt as component (C2) may be, for example, a quaternary ammonium salt or anilinium salt, since it has resistance to substances that may cause inhibition of cationic curing. Examples of the anilinium salt compound include N,N-dialkylanilinium salts such as N,N-dimethylanilinium salt and N,N-diethylanilinium salt.
[0063] The component (C2) may be a quaternary ammonium salt or anilinium salt having an anion containing boron as a constituent element. Commercially available products of such salt compounds include, for example, CXC-1821 (trade name, manufactured by King Industries).
[0064] From the viewpoint of ensuring the formability and curability of the first adhesive layer, the content of the (C2) component may be, for example, 0.1 to 20 parts by mass, 1 to 18 parts by mass, 3 to 15 parts by mass, or 5 to 12 parts by mass per 100 parts by mass of the (C1) component.
[0065] The content of the (C) component may be 5% by mass or more, 10% by mass or more, 15% by mass or more, or 20% by mass or more based on the total mass of the first adhesive layer, from the viewpoint of ensuring the curability of the first adhesive layer. The content of the (C) component may be 70% by mass or less, 60% by mass or less, 50% by mass or less, or 40% by mass or less based on the total mass of the first adhesive layer, from the viewpoint of ensuring the formability of the first adhesive layer. When the content of the (C) component is in the above range, the effects of the present disclosure tend to be significantly exhibited.
[0066] Other Ingredients The first adhesive layer 1 may further contain other components in addition to the component (A), the cured product of the component (B), and the component (C). Examples of the other components include a thermoplastic resin (hereinafter sometimes referred to as "component (D)"), a coupling agent (hereinafter sometimes referred to as "component (E)"), and a filler (hereinafter sometimes referred to as "component (F)").
[0067] Examples of the (D) component include phenoxy resin, polyester resin, polyamide resin, polyurethane resin, polyester urethane resin, acrylic rubber, and epoxy resin (solid at 25°C). When the composition containing the (A), (B), and (C) components further contains the (D) component, the composition layer (and the first adhesive layer 1) can be easily formed from the composition. Among these, the (D) component may be, for example, a phenoxy resin. The content of the (D) component may be 1 mass% or more, 5 mass% or more, or 10 mass% or more, and may be 70 mass% or less, 50 mass% or less, or 30 mass% or less, based on the total mass of the first adhesive layer.
[0068] Examples of the (E) component include silane coupling agents having organic functional groups such as (meth)acryloyl groups, mercapto groups, amino groups, imidazole groups, and epoxy groups, silane compounds such as tetraalkoxysilanes, tetraalkoxytitanate derivatives, and polydialkyltitanate derivatives. The first adhesive layer 1 contains the (E) component, which can further improve the adhesiveness. The (E) component may be, for example, a silane coupling agent. The content of the (E) component may be 0.1 to 10% by mass based on the total mass of the first adhesive layer.
[0069] Examples of the (F) component include non-conductive fillers (e.g., non-conductive particles). The (F) component may be either an inorganic filler or an organic filler. Examples of the inorganic filler include inorganic fine particles such as metal oxide fine particles, such as silica fine particles, alumina fine particles, silica-alumina fine particles, titania fine particles, and zirconia fine particles; and metal nitride fine particles. Examples of the organic filler include organic fine particles, such as silicone fine particles, methacrylate-butadiene-styrene fine particles, acrylic-silicone fine particles, polyamide fine particles, and polyimide fine particles. The (F) component may be, for example, silica fine particles. The content of the (F) component may be 0.1 to 10 mass% based on the total mass of the first adhesive layer.
[0070] Other Additives The first adhesive layer 1 may further contain other additives such as a softener, an accelerator, an anti-degradation agent, a colorant, a flame retardant, a thixotropic agent, etc. The content of the other additives may be, for example, 0.1 to 10 mass % based on the total mass of the first adhesive layer.
[0071] The thickness d1 of the first adhesive layer 1 may be, for example, 30.0 μm or less, 20.0 μm or less, 15.0 μm or less, 10.0 μm or less, 8.0 μm or less, 5.0 μm or less, 4.5 μm or less, 4.0 μm or less, 3.5 μm or less, 3.0 μm or less, or 2.5 μm or less. By having the thickness d1 of the first adhesive layer 1 be 30.0 μm or less, the resin content between the opposing circuits is reduced, and the increase in the connection resistance between the opposing circuits can be suppressed. This tendency is more pronounced when the thickness d1 of the first adhesive layer 1 is 5.0 μm or less. The thickness d1 of the first adhesive layer 1 may be, for example, 0.1 μm or more or 0.7 μm or more. 1, when a portion of the conductive particles 4 is exposed from the surface of the first adhesive layer 1 (for example, protruding toward the second adhesive layer 2), the distance from the surface 1a of the first adhesive layer 1 opposite the second adhesive layer 2 to the boundary S between the first adhesive layer 1 and the second adhesive layer 2 located in the space between adjacent conductive particles 4, 4 (the distance indicated by d1 in FIG. 1) is the thickness of the first adhesive layer 1, and the exposed portion of the conductive particle 4 is not included in the thickness of the first adhesive layer 1. The length of the exposed portion of the conductive particle 4 may be, for example, 0.1 μm or more and 5.0 μm or less.
[0072] The thickness d1 of the first adhesive layer 1 can be determined, for example, by the method described in the Examples. Specifically, the circuit connection adhesive film is sandwiched between two pieces of glass (thickness: about 1 mm), and a resin composition consisting of 100 g of bisphenol A type epoxy resin (product name: JER811, manufactured by Mitsubishi Chemical Corporation) and 10 g of a curing agent (product name: Epomount curing agent, manufactured by Refine Tech Co., Ltd.) is poured into the mold, and the cross section is polished using a polishing machine, and the thickness can be measured using a scanning electron microscope (SEM, product name: SE-8020, manufactured by Hitachi High-Tech Science Corporation). This operation may be performed multiple times, and the average value may be used as the thickness d1 of the first adhesive layer 1.
[0073] The ratio of the thickness of the first adhesive layer 1 to the average particle diameter of the conductive particles 4 (thickness of the first adhesive layer 1 / average particle diameter of the conductive particles 4) may be, for example, 0.30 or more, 0.35 or more, or 0.40 or more. When the ratio is 0.30 or more, the resin content between the opposing circuits is reduced, and an increase in the connection resistance between the opposing circuits can be suppressed. The ratio may be, for example, 2.00 or less, 1.50 or less, 1.20 or less, or 1.00 or less.
[0074] <Second adhesive layer> The second adhesive layer 2 may be, for example, an insulating adhesive layer composed of a non-conductive component (insulating resin component). The second adhesive layer 2 contains a component (C) (second thermosetting resin component) and a component (D). The component (C) contains a component (C1-1), which may contain a component (C1-1a) and a component (C1-1b).
[0075] The (C1) and (C2) components, as well as the (D) component used in the (C) component (i.e., the second thermosetting resin component) in the second adhesive layer 2, are similar to the (C1) and (C2) components, as well as the (D) component used in the (C) component (i.e., the first thermosetting resin component) in the first adhesive layer 1, and therefore detailed explanations thereof will be omitted here.
[0076] The content of component (C) may be 5 mass % or more, 10 mass % or more, 15 mass % or more, or 20 mass % or more based on the total mass of the second adhesive layer from the viewpoint of more excellent connection reliability, and the content of component (C) may be 80 mass % or less, 70 mass % or less, 60 mass % or less, or 50 mass % or less based on the total mass of the second adhesive layer from the viewpoint of preventing resin seepage problems in a reel, which is one embodiment of the supply form.
[0077] From the viewpoint of achieving better connection reliability, the content of the (D) component may be 1 mass % or more, 3 mass % or more, or 5 mass % or more, and may be 60 mass % or less, 40 mass % or less, or 20 mass % or less, based on the total mass of the second adhesive layer.
[0078] From the viewpoint of sufficiently lowering the melt viscosity of the adhesive film for circuit connection and improving the connection reliability of the obtained circuit connection structure, the content of component (D) is 50 parts by mass or less, and may be 48 parts by mass or less, 45 parts by mass or less, 42 parts by mass or less, or 40 parts by mass or less, relative to 100 parts by mass of the total mass of component (C1-1). The content of component (D) may be, for example, 1 part by mass or more, 5 parts by mass or more, 10 parts by mass or more, or 15 parts by mass or more, relative to 100 parts by mass of the total mass of component (C1-1).
[0079] From the standpoint of more sufficiently reducing the melt viscosity of the adhesive film for circuit connection and further improving the connection reliability of the resulting circuit connection structure, the content of component (D) may be at least 50 parts by mass, at least 55 parts by mass, or at least 60 parts by mass, and may be at most 150 parts by mass, at most 120 parts by mass, or at most 100 parts by mass, relative to 100 parts by mass of the total mass of component (C1-1a).
[0080] From the standpoint of more sufficiently reducing the melt viscosity of the adhesive film for circuit connection and further improving the connection reliability of the resulting circuit connection structure, the content of component (D) may be no more than 120 parts by mass, no more than 110 parts by mass, or no more than 100 parts by mass, or may be no less than 30 parts by mass, no less than 40 parts by mass, or no less than 50 parts by mass, relative to 100 parts by mass of the total mass of component (C1-1b).
[0081] The total content of the (C1-1) component and the (D) component may be 15 mass % or more, 20 mass % or more, or 25 mass % or more, and may be 50 mass % or less, 40 mass % or less, or 35 mass % or less, based on the total mass of the second adhesive layer, from the viewpoint of more sufficiently reducing the melt viscosity of the adhesive film for circuit connection and further improving the connection reliability of the obtained circuit connection structure.
[0082] The second adhesive layer 2 may further contain other components and other additives than those in the first adhesive layer 1. Preferred aspects of the other components and other additives are the same as those of the first adhesive layer 1.
[0083] The content of the component (E) may be 0.1 to 10 mass % based on the total mass of the second adhesive layer.
[0084] The content of the (F) component may be 1 mass % or more, 10 mass % or more, or 30 mass % or more, and may be 90 mass % or less, 70 mass % or less, or 50 mass % or less, based on the total mass of the second adhesive layer.
[0085] The content of the other additives may be, for example, 0.1 to 10% by mass based on the total mass of the second adhesive layer.
[0086] The thickness d2 of the second adhesive layer 2 may be appropriately set according to the height of the electrodes of the circuit member to be bonded. The thickness d2 of the second adhesive layer 2 may be 1.0 μm or more, 3.0 μm or more, or 5.0 μm or more, and may be 30.0 μm or less, 20.0 μm or less, 15.0 μm or less, or 13.0 μm or less, from the viewpoint of being able to sufficiently fill the space between the electrodes to seal the electrodes and obtain better connection reliability. In addition, when a part of the conductive particles 4 is exposed from the surface of the first adhesive layer 1 (for example, protruding to the second adhesive layer 2 side), the distance (distance shown as d2 in FIG. 1) from the surface 2a of the second adhesive layer 2 opposite to the first adhesive layer 1 side to the boundary S between the first adhesive layer 1 and the second adhesive layer 2 located in the space between the adjacent conductive particles 4, 4 is the thickness of the second adhesive layer 2.
[0087] The thickness d2 of the second adhesive layer 2 can be determined, for example, in the same manner as the method for measuring the thickness d1 of the first adhesive layer 1 described above.
[0088] The thickness of the adhesive film 10A for circuit connection (the total thickness of all layers constituting the adhesive film 10A for circuit connection; in FIG. 1, the total thickness d1 of the first adhesive layer 1 and the thickness d2 of the second adhesive layer 2) may be, for example, 3.0 μm or more, 5.0 μm or more, or 7.0 μm or more, and may be 60.0 μm or less, 40.0 μm or less, 30.0 μm or less, 20.0 μm or less, or 15.0 μm or less.
[0089] From the viewpoint of further improving the connection reliability of the circuit connection structure, the minimum melt viscosity of the adhesive film for circuit connection 10A may be, for example, 400 Pa·s or less. The minimum melt viscosity of the adhesive film for circuit connection 10A may be 350 Pa·s or less, 300 Pa·s or less, 250 Pa·s or less, or 200 Pa·s or less, or may be 10 Pa·s or more, 30 Pa·s or more, or 50 Pa·s or more. The minimum melt viscosity of the adhesive film for circuit connection 10A tends to depend mainly on the properties of the second adhesive layer.
[0090] The melt viscosity of the adhesive film for circuit connection 10A at 60°C may be, for example, 3500 Pa·s or less, from the viewpoint of further improving the connection reliability of the circuit connection structure. The melt viscosity of the adhesive film for circuit connection 10A at 60°C may be 3000 Pa·s or less, 2500 Pa·s or less, 2000 Pa·s or less, or 1500 Pa·s or less, or may be 100 Pa·s or more, 300 Pa·s or more, or 500 Pa·s or more. The melt viscosity of the adhesive film for circuit connection 10A at 60°C tends to depend mainly on the properties of the second adhesive layer.
[0091] In this specification, the melt viscosity can be measured as follows. First, the adhesive film for circuit connection is laminated with a laminator so that the thickness is 500 μm or more to obtain a laminate. The obtained laminate is cut into 10.0 mm × 10.0 mm to obtain a measurement sample. The obtained measurement sample is measured using a viscoelasticity measuring device under conditions of a temperature rise rate of 10 ° C. / min, a measurement frequency of 10 Hz, and a measurement temperature of 40 to 200 ° C., and the minimum melt viscosity, which is the minimum value within the measurement temperature range, and the melt viscosity at 60 ° C. are derived.
[0092] The adhesive film 10A for circuit connection is an adhesive film used for connecting circuits. The adhesive film 10A for circuit connection may or may not have anisotropic conductivity. That is, the adhesive film for circuit connection may be an anisotropically conductive adhesive film or a non-anisotropically conductive (e.g., isotropically conductive) adhesive film. The adhesive film 10A for circuit connection may be interposed between a first circuit member having a first electrode (the surface on which the first electrode is provided) and a second circuit member having a second electrode (the surface on which the second electrode is provided), and may be used to electrically connect the first electrode and the second electrode to each other (through conductive particles (or a molten and solidified product of conductive particles)) by thermocompression bonding the first circuit member and the second circuit member (heating a laminate including the first circuit member, the adhesive film 10A for circuit connection, and the second circuit member while pressing them in the thickness direction of the laminate).
[0093] The adhesive film 10A for circuit connection can reduce the melt viscosity, which can suppress a decrease in resin fluidity and a decrease in resin expulsion even when mounted at low temperature and pressure, making it possible to form a circuit connection structure with excellent connection reliability.
[0094] Although the adhesive film for circuit connection of the present embodiment has been described above, the present disclosure is not limited to the above embodiment.
[0095] 2 is a schematic cross-sectional view showing another embodiment of the adhesive film for circuit connection, and is a diagram showing a schematic longitudinal section of the adhesive film for circuit connection. The adhesive film for circuit connection may be composed of two layers, for example, a first adhesive layer and a second adhesive layer, or may be composed of three or more layers including two layers, that is, a first adhesive layer and a second adhesive layer. The adhesive film for circuit connection may further include, for example, a third adhesive layer 5 provided on the opposite side of the first adhesive layer to the second adhesive layer, as in the adhesive film for circuit connection 10B shown in FIG. 2.
[0096] The third adhesive layer 5 contains at least the (C) component. The (C1) and (C2) components used in the (C) component (i.e., the third thermosetting resin component) in the third adhesive layer are similar to the (C1) and (C2) components used in the (C) component (i.e., the first thermosetting resin component) in the first adhesive layer 1, and therefore detailed description thereof will be omitted here. The third thermosetting resin component may be the same as or different from the first thermosetting resin component. The third thermosetting resin component may be the same as or different from the second thermosetting resin component.
[0097] The content of the (C) component may be 5% by mass or more, 10% by mass or more, 15% by mass or more, or 20% by mass or more based on the total mass of the third adhesive layer from the viewpoint of imparting good transferability and peel resistance. The content of the (C) component may be 70% by mass or less, 60% by mass or less, 50% by mass or less, or 40% by mass or less based on the total mass of the third adhesive layer from the viewpoint of imparting good half-cut properties and blocking resistance (suppression of resin bleeding from the reel).
[0098] The third adhesive layer 5 may further contain other components and other additives than those in the first adhesive layer 1. Preferred aspects of the other components and other additives are the same as those of the first adhesive layer 1.
[0099] The content of the (D) component may be 10 mass% or more, 20 mass% or more, or 30 mass% or more, and may be 80 mass% or less, 70 mass% or less, or 60 mass% or less, based on the total mass of the third adhesive layer.
[0100] The content of the component (E) may be 0.1 to 10 mass % based on the total mass of the third adhesive layer.
[0101] The content of the (F) component may be 1 mass% or more, 3 mass% or more, or 5 mass% or more, and may be 50 mass% or less, 40 mass% or less, or 30 mass% or less, based on the total mass of the third adhesive layer.
[0102] The content of the other additives may be, for example, 0.1 to 10% by mass based on the total mass of the third adhesive layer.
[0103] The thickness d3 of the third adhesive layer 5 may be appropriately set according to the height of the electrodes of the circuit member to be bonded. The thickness d3 of the third adhesive layer 5 may be 0.2 μm or more or 0.5 μm or more, and 5.0 μm or less or 2.5 μm or less, from the viewpoint of being able to sufficiently fill the space between the electrodes to seal the electrodes and obtain better connection reliability. The thickness d3 of the third adhesive layer 5 is the distance from the surface 5a of the third adhesive layer 5 opposite the first adhesive layer 1 side to the surface 1a of the first adhesive layer 1 opposite the second adhesive layer 2 side (the distance indicated by d3 in FIG. 2).
[0104] The thickness d3 of the third adhesive layer 5 can be determined, for example, in the same manner as the method for measuring the thickness d1 of the first adhesive layer 1 described above.
[0105] When the adhesive film for circuit connection has a layer other than the first adhesive layer and the second adhesive layer (e.g., a third adhesive layer), the thickness of the adhesive film for circuit connection (the sum of the thicknesses of all layers constituting the adhesive film for circuit connection) may be within the same range as the possible thickness of the adhesive film for circuit connection 10A described above.
[0106] [Method of manufacturing circuit connecting adhesive film] A manufacturing method of an adhesive film for circuit connection in one embodiment may include a step (first step) of forming a first adhesive layer containing component (A), and a step (second step) of laminating a second adhesive layer containing component (C) on the first adhesive layer.
[0107] In the first step, for example, first, a first adhesive composition containing components (A), (B), and (C) (first thermosetting resin component), other components, other additives, etc. is dissolved or dispersed in an organic solvent by stirring, mixing, kneading, etc. to prepare a first varnish composition. Then, the first varnish composition is applied to a substrate that has been subjected to a release treatment using a knife coater, roll coater, applicator, comma coater, die coater, etc., and the organic solvent is volatilized by heating to form a composition layer made of the first adhesive composition on the substrate. At this time, the thickness of the first adhesive layer finally obtained can be adjusted by adjusting the amount of the varnish composition applied.
[0108] When the composition layer contains the (B) component, the first step may be a step of curing the (B) component in the composition layer by irradiating the composition layer made of the first adhesive composition with light (active light rays) to form an adhesive layer containing the (A) component, a cured product of the (B) component, the (C) component, other components, other additives, etc. The first adhesive layer can be called a first adhesive film.
[0109] The organic solvent used in the preparation of the first varnish composition is not particularly limited as long as it has the property of dissolving or dispersing each component uniformly. Examples of such organic solvents include toluene, acetone, methyl ethyl ketone, methyl isobutyl ketone, ethyl acetate, propyl acetate, and butyl acetate. These organic solvents can be used alone or in combination of two or more. The stirring and mixing or kneading in the preparation of the first varnish composition can be performed using, for example, a stirrer, a grinding machine, a three-roll mill, a ball mill, a bead mill, a homodisper, or the like.
[0110] The substrate is not particularly limited as long as it has heat resistance that can withstand the heating conditions when volatilizing the organic solvent. Examples of such substrates include substrates (e.g., films) made of oriented polypropylene (OPP), polyethylene terephthalate (PET), polyethylene naphthalate, polyethylene isophthalate, polybutylene terephthalate, polyolefin, polyacetate, polycarbonate, polyphenylene sulfide, polyamide, polyimide, cellulose, ethylene-vinyl acetate copolymer, polyvinyl chloride, polyvinylidene chloride, synthetic rubber, liquid crystal polymer, and the like.
[0111] The heating conditions for volatilizing the organic solvent from the first varnish composition applied to the substrate can be appropriately set according to the organic solvent used, etc. The heating conditions may be, for example, at 40 to 120° C. for 0.1 to 10 minutes.
[0112] A part of the organic solvent may remain in the first adhesive layer without being removed. The content of the organic solvent in the first adhesive layer may be, for example, 10 mass % or less based on the total mass of the first adhesive layer.
[0113] For the light irradiation, light having a wavelength in the range of 150 to 750 nm (for example, ultraviolet light) can be used. For example, light irradiation can be performed using a low pressure mercury lamp, a medium pressure mercury lamp, a high pressure mercury lamp, an ultra-high pressure mercury lamp, a xenon lamp, a metal halide lamp, an LED light source, or the like. The integrated light amount of the light to be irradiated can be appropriately set, but is, for example, 500 to 3000 mJ / cm. 2 It may be.
[0114] The second step is a step of laminating a second adhesive layer on the first adhesive layer. In the second step, for example, a second varnish composition is prepared in the same manner as in the first step, except that a second adhesive composition containing the (C) component (second thermosetting resin component), the (D) component, other components, other additives, etc. is used (and light irradiation is not performed), and a second adhesive layer is formed on a substrate to obtain a second adhesive film. Next, the first adhesive layer (first adhesive film) and the second adhesive layer (second adhesive film) are bonded together to laminate the second adhesive layer on the first adhesive layer. In addition, in the second step, for example, the second adhesive layer can also be laminated on the first adhesive layer by directly applying the second varnish composition on the first adhesive layer and volatilizing the organic solvent.
[0115] A part of the organic solvent may remain in the second adhesive layer without being removed. The content of the organic solvent in the second adhesive layer may be, for example, 10 mass % or less based on the total mass of the second adhesive layer.
[0116] Examples of the method for bonding the first adhesive layer (first adhesive film) and the second adhesive layer (second adhesive film) include hot pressing, roll lamination, vacuum lamination, etc. These bonding methods can be performed under temperature conditions of, for example, 0 to 80°C.
[0117] While one embodiment of the method for producing an adhesive film for circuit connection has been described above by taking the method for producing the adhesive film for circuit connection 10A as an example, the present disclosure is not limited to the above embodiment.
[0118] For example, the method for producing an adhesive film for circuit connection may further include a step (third step) of laminating a third adhesive layer on the surface of the first adhesive layer opposite to the second adhesive layer. According to such a production method, it is possible to obtain an adhesive film for circuit connection further including a third adhesive layer (for example, adhesive film 10B for circuit connection shown in FIG. 2).
[0119] The third adhesive layer can be formed using a third adhesive composition containing the (C) component (third thermosetting resin component), other components, other additives, etc. In the third step, for example, a third varnish composition is prepared in the same manner as in the first step, except that the third adhesive composition is used (and light irradiation is not performed), and a third adhesive layer is formed on a substrate to obtain a third adhesive film. Next, the first adhesive layer (first adhesive film) and the third adhesive layer (third adhesive film) are bonded together to laminate the third adhesive layer on the first adhesive layer. In addition, in the third step, for example, the third adhesive layer can also be laminated on the first adhesive layer by directly applying the third varnish composition on the first adhesive layer and volatilizing the organic solvent.
[0120] [Circuit connection structure and method for producing same] The circuit connection structure and the method for producing the same will be described below by taking as an example an embodiment in which the above-mentioned adhesive film 10A for circuit connection is used as the circuit connecting material.
[0121] Fig. 3 is a schematic cross-sectional view showing one embodiment of a circuit connection structure. As shown in Fig. 3, the circuit connection structure 100 includes a first circuit board 21 and a first circuit member 23 having a first electrode 22 formed on the main surface 21a of the first circuit board 21, a second circuit member 26 having a second electrode 25 formed on the main surface 24a of the second circuit board 24, and a circuit connection part 27 that includes a cured body of the circuit connection adhesive film 10A, is disposed between the first circuit member 23 and the second circuit member 26, electrically connects the first electrode 22 and the second electrode 25 to each other via the conductive particles 4 (or a melted and solidified product of the conductive particles 4), and bonds the first circuit member 23 and the second circuit member 26.
[0122] The first circuit member 23 and the second circuit member 26 may be the same or different from each other. The first circuit member 23 and the second circuit member 26 may be a glass substrate or a plastic substrate on which electrodes are formed, a printed wiring board, a ceramic wiring board, a flexible wiring board, an IC chip, or the like. The first circuit board 21 and the second circuit board 24 may be formed of an inorganic material such as a semiconductor, glass, or ceramic, an organic material such as polyimide or polycarbonate, or a composite material such as glass / epoxy. Among these, since the circuit connection adhesive film 10A can be suitably used for COP mounting, the first circuit member 23 may be, for example, a plastic substrate made of an organic material such as polyimide, polycarbonate, polyethylene terephthalate, or cycloolefin polymer, and the second circuit board 24 may be, for example, an IC chip.
[0123] The first electrode 22 and the second electrode 25 may be electrodes containing metals such as gold, silver, tin, ruthenium, rhodium, palladium, osmium, iridium, platinum, copper, aluminum, molybdenum, titanium, and oxides such as indium tin oxide (ITO), indium zinc oxide (IZO), and indium gallium zinc oxide (IGZO). The first electrode 22 and the second electrode 25 may be electrodes formed by laminating two or more of these metals, oxides, and the like. An electrode formed by laminating two or more of these may have two or more layers, or three or more layers. When the first circuit member 23 is a plastic substrate, the first electrode 22 may be an electrode having a titanium layer on the outermost surface. The first electrode 22 and the second electrode 25 may be circuit electrodes or bump electrodes. At least one of the first electrode 22 and the second electrode 25 may be a bump electrode. The circuit connection structure shown in FIG. 3 is an embodiment in which the first electrode 22 is a circuit electrode and the second electrode 25 is a bump electrode.
[0124] The circuit connection portion 27 includes a cured body of the adhesive film 10A for circuit connection. The circuit connection portion 27 may be made of a cured body of the adhesive film 10A for circuit connection. The circuit connection portion 27 has, for example, a first cured body region 28 located on the first circuit member 23 side in the direction in which the first circuit member 23 and the second circuit member 26 face each other (hereinafter referred to as the "facing direction") and made of a cured body derived from the first adhesive layer other than the conductive particles 4, a second cured body region 29 located on the second circuit member 26 side in the facing direction and made of a cured body derived from the second adhesive layer, and conductive particles 4 interposed at least between the first electrode 22 and the second electrode 25 to electrically connect the first electrode 22 and the second electrode 25 to each other. As shown in FIG. 3, the circuit connection portion 27 does not have to have two distinct hardened body regions, the first hardened body region 28 and the second hardened body region 29, but may have a single hardened body region in which the hardened body derived from the first adhesive layer and the hardened body derived from the second adhesive layer are mixed.
[0125] Fig. 4 is a schematic cross-sectional view showing one embodiment of a method for producing a circuit connection structure. Fig. 4(a) and Fig. 4(b) are schematic cross-sectional views showing each step. As shown in Fig. 4, the method for producing a circuit connection structure 100 includes a step of interposing an adhesive film for circuit connection 10A between a first circuit member 23 having a first electrode 22 and a second circuit member 26 having a second electrode 25, and thermocompressing the first circuit member 23 and the second circuit member 26 to electrically connect the first electrode 22 and the second electrode 25 to each other.
[0126] Specifically, first, a first circuit member 23 including a first circuit board 21 and a first electrode 22 formed on a main surface 21a of the first circuit board 21, and a second circuit member 26 including a second circuit board 24 and a second electrode 25 formed on a main surface 24a of the second circuit board 24 are prepared.
[0127] Next, the first circuit member 23 and the second circuit member 26 are arranged so that the first electrode 22 and the second electrode 25 face each other, and the adhesive film for circuit connection 10A is arranged between the first circuit member 23 and the second circuit member 26. For example, as shown in FIG. 4(a), the adhesive film for circuit connection 10A is laminated on the first circuit member 23 so that the first adhesive layer 1 side faces the main surface 21a of the first circuit board 21. Next, the second circuit member 26 is arranged on the first circuit member 23 on which the adhesive film for circuit connection 10A is laminated so that the first electrode 22 on the first circuit board 21 and the second electrode 25 on the second circuit board 24 face each other.
[0128] Then, as shown in FIG. 4(b), the first circuit member 23, the circuit connection adhesive film 10A, and the second circuit member 26 are heated while the first circuit member 23 and the second circuit member 26 are pressed in the thickness direction to thermocompress the first circuit member 23 and the second circuit member 26 together. At this time, as shown by the arrow in FIG. 4(b), the second adhesive layer 2 contains a flowable uncured thermosetting resin component, so that it flows to fill the gaps between the second electrodes 25 and is cured by the heat of the thermocompression bonding. As a result, the first electrode 22 and the second electrode 25 are electrically connected to each other via the conductive particles 4, and the first circuit member 23 and the second circuit member 26 are bonded to each other, thereby obtaining the circuit connection structure 100 shown in FIG. 2.
[0129] In the manufacturing method of the circuit connection structure 100 of this embodiment, the first adhesive layer 1 can be said to be a layer in which a part of the first adhesive layer 1 is hardened by light irradiation, so that the conductive particles 4 are fixed in the first adhesive layer 1, and the first adhesive layer 1 hardly flows during thermocompression bonding, and the conductive particles are efficiently captured between the opposing electrodes, thereby reducing the connection resistance between the opposing first electrode 22 and second electrode 25. In addition, since the thickness of the first adhesive layer is 5.0 μm or less and the ratio of the thickness of the first adhesive layer to the average particle size of the conductive particles is 0.50 or more, the resin content between the opposing circuits is reduced, and an increase in the connection resistance between the opposing circuits can be suppressed.
[0130] The heating temperature in thermocompression bonding can be set appropriately, and may be, for example, 50 to 190°C. In the case of COP mounting, the heating temperature may be, for example, 120 to 170°C. The pressure is not particularly limited as long as it is within a range that does not damage the adherend, and in the case of COP mounting, the area-equivalent pressure at the bump electrode may be, for example, 25 MPa or less, or may be 0.1 to 20 MPa. In addition, in the case of COG mounting, the area-equivalent pressure at the bump electrode may be, for example, 10 to 100 MPa. The heating and pressurizing time may be in the range of 0.5 to 120 seconds. EXAMPLES
[0131] The present disclosure will be described in more detail below with reference to examples, although the present disclosure is not limited to these examples.
[0132] [Material preparation] Synthesis of cationic polymerizable compound C1-1a-1 In a 300 mL eggplant flask, 4.71 g (42.0 mmol) of 3-cyclohexene-1-methanol (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) and 50 mL of dimethylformamide (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) were placed and cooled to 5°C on ice while stirring. Then, 4.71 g (42.0 mmol) of potassium tert-butoxide (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) was added at 5°C, and 4.87 g (20.0 mmol) of 3,3-bis(bromomethyl)oxetane (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) was added dropwise. Then, the temperature was raised to room temperature (25°C) and stirred for 14 hours. Then, toluene (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) was added to this reaction solution, and after washing with water, the organic solvent was distilled off from the obtained organic layer. The obtained concentrate was purified by distillation to obtain 3.98 g (13.0 mol / yield 65%) of 3,3-bis[(3-cyclohexen-1-ylmethoxy)methyl]oxetane) as a colorless transparent liquid.
[0133] In a 300mL eggplant flask, 3.98g (13.0mmol) of 3,3-bis[(3-cyclohexen-1-ylmethoxy)methyl]oxetane, 0.53g (3.90mmol) of potassium carbonate (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.), 4mL of acetonitrile (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.), and 6mL of methanol (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) were placed and stirred at room temperature (25°C). Then, 5.19g (45.5mmol) of 30% aqueous hydrogen peroxide solution (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) was added dropwise and stirred for 18 hours. 50g of toluene was added to this reaction solution, and the product was extracted and washed with water. The organic solvent was distilled off from the obtained organic layer, and the obtained concentrate was purified by silica gel column chromatography (ethyl acetate / hexane=2 / 8 (volume ratio)) to obtain 2.54 g (7.50 mmol / yield 58%) of 3,3-bis[(3,4-epoxycyclohexyl-1-methoxy)methyl]oxetane as a colorless transparent liquid.
[0134] In the examples and comparative examples, the materials shown below were used as component (A), component (B), component (C), component (D), component (E), and component (F).
[0135] (A) Component: Conductive particles Conductive particle A-1: Conductive particle with a plastic core surface plated with Ni and a top surface plated with Pd (average particle size: 3.2 μm)
[0136] (B) Component: Photocurable resin component Component (B1): radically polymerizable compound Radical polymerizable compound B1-1: VR-90 (bisphenol A type epoxy (meth)acrylate (bifunctional) (vinyl ester resin), manufactured by Showa Denko K.K.) Radical polymerizable compound B1-2: A-1000 (polyethylene glycol diacrylate (bifunctional), manufactured by Shin-Nakamura Chemical Co., Ltd.) Component (B2): Photoradical polymerization initiator Photoradical polymerization initiator B2-1: Omnirad 907 (a compound having an α-aminoalkylphenone structure, manufactured by IGM Resins)
[0137] (C) Component: Thermosetting resin component Component (C1): Cationic polymerizable compound Component (C1-1): Alicyclic epoxy compound Component (C1-1a): First alicyclic epoxy compound Cationic polymerizable compound C1-1a-1: 3,3-bis[(3,4-epoxycyclohexyl-1-methoxy)methyl]oxetane synthesized above (liquid at 25°C) Cationic polymerizable compound C1-1a-2: Celloxide 2021P (manufactured by Daicel Corporation, liquid at 25°C) Component (C1-1b): Second alicyclic epoxy compound Cationic polymerizable compound C1-1b-1: EHPE3150 (manufactured by Daicel Corporation, solid at 25°C) Component (C1-2): a cationically polymerizable compound other than component (C1-1) Cationic polymerizable compound C1-2-1: ETERNACOLL OXBP (oxetane compound, manufactured by Ube Industries, Ltd.) Cationic polymerizable compound C1-2-2: OXT-212 (oxetane compound, manufactured by Toagosei Co., Ltd.) Cationic polymerizable compound C1-2-3: jER1007 (epoxy compound, manufactured by Mitsubishi Chemical Corporation) Component (C2): Thermal cationic polymerization initiator Thermal cationic polymerization initiator C2-1: CXC-1821 (N-(p-methoxybenzyl)-N,N-dimethylanilinium tetrakis(pentafluorophenyl)borate, manufactured by King Industries)
[0138] (D) Component: Thermoplastic resin Thermoplastic resin D-1: Phenototo FX-293 (phenoxy resin, manufactured by Nippon Steel Chemical & Material Co., Ltd.) Thermoplastic resin D-2: Phenototo YP-70 (phenoxy resin, manufactured by Nippon Steel Chemical & Material Co., Ltd.)
[0139] Component (E): Coupling agent Coupling agent E-1: SH-6040 (3-glycidoxypropyltrimethoxysilane, manufactured by Dow Corning Toray Co., Ltd.) Coupling agent E-2: KBM-303 (ethyltrimethoxysilane, manufactured by Shin-Etsu Chemical Co., Ltd.)
[0140] (F) Ingredient: Filler Filler F-1: ADMAFINE SE2050 (silica particles, manufactured by ADMATECHS Co., Ltd.) Filler F-2: Aerosil R805 (silica fine particles, manufactured by Evonik Industries AG)
[0141] Example 1 [Preparation of adhesive film for circuit connection] <Preparation of first adhesive film (first adhesive layer)> The materials shown in Table 1 were mixed in the amounts shown in Table 1 (the values in Table 1 indicate the non-volatile content) to obtain a first varnish composition. Next, the first varnish composition was applied to a release-treated PET (polyethylene terephthalate) film having a thickness of 50 μm, which was a substrate that had been subjected to a release treatment, while applying a magnetic field, and the organic solvent and the like were dried to obtain a composition layer containing each component. Next, the composition layer was irradiated with light (UV irradiation: metal halide lamp, accumulated light amount: 2000 mJ / cm2). 2 (wavelength: 365 nm) to obtain a first adhesive film 1A (first adhesive layer 1A). The first adhesive film 1A contains conductive particles, a cured product of a photocurable resin component, and a thermosetting resin component.
[0142] [Table 1]
[0143] <Preparation of second adhesive film (second adhesive layer)> A second varnish composition was obtained by mixing the materials shown in Table 2 in the amounts shown in Table 2 (the values in Table 2 indicate the non-volatile content). Next, the composition was applied onto a release-treated PET (polyethylene terephthalate) film with a thickness of 50 μm, which was a release-treated substrate, and the organic solvent was dried to obtain a second adhesive film 2A (second adhesive layer 2A).
[0144] [Table 2]
[0145] <Preparation of adhesive film for circuit connection> Using the first adhesive film 1A (first adhesive layer 1A) and second adhesive film 2A (second adhesive layer 2A) prepared above, the first adhesive film 1A (first adhesive layer 1A) and the second adhesive film 2A (second adhesive layer 2A) were bonded together using a hot roll laminator heated to 50°C to obtain an adhesive film for circuit connection of Example 1.
[0146] [Measurement of thickness of each adhesive layer] The thickness of the first adhesive layer and the second adhesive layer was measured for the circuit connection adhesive film of Example 1. In the measurement, the circuit connection adhesive film was sandwiched between two pieces of glass (thickness: about 1 mm), and a resin composition consisting of 100 g of bisphenol A type epoxy resin (product name: JER811, manufactured by Mitsubishi Chemical Corporation) and 10 g of a curing agent (product name: Epomount curing agent, manufactured by Refine Tech Co., Ltd.) was poured into the mold, and the cross section was polished using a polishing machine, and the thickness of the first adhesive layer and the second adhesive layer was measured using a scanning electron microscope (SEM, product name: SE-8020, manufactured by Hitachi High-Tech Science Corporation). The results are shown in Table 4.
[0147] [Melt viscosity measurement] The melt viscosity was measured for the adhesive film for circuit connection of Example 1. The adhesive film for circuit connection was laminated with a laminator to a thickness of 500 μm or more to obtain a laminate. The obtained laminate was cut into 10.0 mm × 10.0 mm to obtain a measurement sample. The obtained measurement sample was measured using a viscoelasticity measuring device (product name: ARES-G2, manufactured by TA Instruments) under conditions of a temperature rise rate of 10 ° C. / min, a measurement frequency of 10 Hz, and a measurement temperature of 40 to 200 ° C., and the minimum melt viscosity, which is the minimum value within the measurement temperature range, and the melt viscosity at 60 ° C. were derived. The results are shown in Table 4.
[0148] [Measurement of substrate peel strength] First, a glass substrate (thickness 0.5 mm) with ITO (indium tin oxide) was prepared. The circuit connection adhesive film of Example 1 was cut to a width of 2 mm and a length of 23 mm, and the cut-out circuit connection adhesive film was placed on the glass substrate so that the first adhesive layer was in contact with the ITO surface to obtain a laminate. Next, the obtained laminate was heated and pressed in the lamination direction using a thermal temporary pressure bonding device (LD-06, manufactured by Ohashi Seisakusho Co., Ltd.) consisting of a ceramic stage and a metal pressure bonding head (8 mm x 50 mm) with a built-in heater, to perform temporary fixing, and was used as a measurement sample. The heating temperature for temporary fixing was 60°C at the temperature of the first adhesive layer, the pressing time was 1 second, and the pressing pressure was 1 MPa. The obtained measurement sample was peeled off from the glass substrate using a Tensilon universal testing machine (STA-1150, manufactured by A & D Co., Ltd.) under the conditions of a peel angle of 90° and a peel speed of 50 mm / min, to obtain the substrate peel strength. The results are shown in Table 4.
[0149] [Connection reliability test] (Fabrication of circuit connection structure) A circuit connection structure was produced using the circuit connection adhesive film of Example 1. The circuit connection adhesive film was cut into a width of 2.0 mm, and the circuit connection adhesive film was placed on the first circuit member so that the first adhesive layer and the first circuit member (plastic substrate) were in contact with each other. Using a thermal temporary pressure bonding device (LD-06, manufactured by Ohashi Seisakusho Co., Ltd.) consisting of a stage made of a ceramic heater and a tool (8 mm x 50 mm), heating and pressure were applied for 1 second under conditions of 60°C and 1 MPa to attach the circuit connection adhesive film to the first circuit member, and the PET film on the opposite side of the circuit connection adhesive film from the first circuit member was peeled off. Next, the bump electrodes of the first circuit component and the circuit electrodes of the second circuit component (IC chip) were aligned, and then using a heat tool measuring 8 mm x 45 mm, heating and pressurization was performed for 5 seconds under conditions of a connection temperature of 160°C and an area-equivalent pressure of 17 MPa at the bump electrode, using 50 μm thick Teflon (registered trademark) as a cushioning material, to attach the second adhesive layer of the circuit connection adhesive film to the second circuit component, thereby producing a circuit connection structure.
[0150] (Evaluation of connection resistance) The connection resistance was evaluated using the circuit connection structure of Example 1. The connection resistance was evaluated by a four-terminal measurement method immediately after the production of the circuit connection structure and after a high-temperature, high-humidity test, and was evaluated using the average value of the connection resistance values measured at 14 points. The high-temperature, high-humidity test was performed by treating the circuit connection structure for 500 hours in a high-temperature, high-humidity test chamber at a temperature of 85°C and a humidity of 85% RH. For the measurement, a constant current (1 mA) was applied between the circuit electrode of the first circuit member and the circuit electrode of the second circuit member (connection portion) of the circuit connection structure using a direct current power supply device 6243 manufactured by ADC Corporation. The potential difference of the connection portion when the current was applied was measured at any 14 points using a digital multimeter (7461A, manufactured by ADC Corporation), and the average value was calculated. Immediately after the fabrication of the circuit connection structure, a connection resistance value of 1.00Ω or less was rated as "S" for superior connection resistance, a connection resistance value of more than 1.00Ω but less than 1.20Ω was rated as "A", and a connection resistance value of more than 1.20Ω was rated as "B". After the high temperature and high humidity test, a connection resistance value of 1.20Ω or less was rated as "S" for superior connection resistance, a connection resistance value of more than 1.20Ω but less than 1.30Ω was rated as "A", and a connection resistance value of more than 1.30Ω was rated as "B". The results are shown in Table 4.
[0151] (Examples 2 to 5 and Comparative Example 1) In <Preparation of the second adhesive film (second adhesive layer)>, the second varnish composition was prepared in the same manner as in Example 1, except that the type and / or amount of the material to be blended was changed as shown in Table 3. Then, in the same manner as in Example 1, the second adhesive layers 2B to 2F were laminated on the first adhesive layer 1A, respectively, to prepare two-layer circuit connection adhesive films of Examples 2 to 5 and Comparative Example 1. For the circuit connection adhesive films of Examples 2 to 5 and Comparative Example 1, the thickness, melt viscosity, and substrate peel strength of each adhesive layer were determined in the same manner as in Example 1. In addition, a circuit connection structure was prepared and a connection reliability test was performed in the same manner as in Example 1. The results are shown in Table 4.
[0152] [Table 3]
[0153] [Table 4]
[0154] As shown in Table 4, the adhesive films for circuit connection of Examples 1 to 5, in which the content of thermoplastic resin was 50 parts by mass or less relative to 100 parts by mass of the total mass of the alicyclic epoxy compound, were superior to the adhesive film for circuit connection of Comparative Example 1, which did not satisfy this requirement, particularly in terms of connection resistance after high temperature and high humidity testing. These results confirmed that the adhesive film for circuit connection of the present disclosure is capable of forming a circuit connection structure with excellent connection reliability. [Explanation of symbols]
[0155] 1...first adhesive layer, 2...second adhesive layer, 3...adhesive component, 4...conductive particles, 5...third adhesive layer, 10A, 10B...adhesive film for circuit connection, 21...first circuit board, 22...first electrode (circuit electrode), 23...first circuit member, 24...second circuit board, 25...second electrode (bump electrode), 26...second circuit member, 27...circuit connection part, 100...circuit connection structure.
Claims
1. a first adhesive layer containing conductive particles; a second adhesive layer provided on the first adhesive layer; Equipped with The second adhesive layer contains a thermosetting resin component and a thermoplastic resin, the thermosetting resin component comprises an alicyclic epoxy compound, The content of the thermoplastic resin is 50 parts by mass or less relative to 100 parts by mass of the total mass of the alicyclic epoxy compound. Adhesive film for circuit connection.
2. The total content of the alicyclic epoxy compound and the thermoplastic resin is 15 mass% or more based on the total mass of the second adhesive layer.
2. The adhesive film for circuit connection according to claim 1.
3. the thermosetting resin component contains, as the alicyclic epoxy compound, a first alicyclic epoxy compound that is liquid at 25° C. and a second alicyclic epoxy compound that is solid at 25° C.; 3. The adhesive film for circuit connection according to claim 1 or 2.
4. The content of the thermoplastic resin is 120 parts by mass or less relative to 100 parts by mass of the total mass of the second alicyclic epoxy compound. The adhesive film for circuit connection according to claim 3 .
5. The content of the thermoplastic resin is 50 parts by mass or more relative to 100 parts by mass of the total mass of the first alicyclic epoxy compound. The adhesive film for circuit connection according to claim 3 .
6. the thermosetting resin component further contains a cationic polymerizable compound other than the alicyclic epoxy compound; 3. The adhesive film for circuit connection according to claim 1 or 2.
7. a step of interposing the adhesive film for circuit connection according to claim 1 or 2 between a first circuit member having a first electrode and a second circuit member having a second electrode, and thermocompressing the first circuit member and the second circuit member to electrically connect the first electrode and the second electrode to each other, A method for manufacturing a circuit connection structure.
8. a first circuit member having a first electrode; a second circuit member having a second electrode; a circuit connection portion disposed between the first circuit member and the second circuit member, the circuit connection portion electrically connecting the first electrode and the second electrode to each other; Equipped with The circuit connection portion comprises a cured product of the adhesive film for circuit connection according to claim 1 or 2. Circuit connection structure.
Citation Information
Patent Citations
Connection body, manufacturing method therefor, electronic component connection method and electronic component
JP2016054288A